(untitled) (Global Journal of Human-Social Science, 2021)
Developing country like Bangladesh, it is an unarguable fact that the development of a nation is dependent on education of its people. The purpose of this research is to determine the fundamental issues that act behind high dropouts in primary and followed by secondary level in Bangladesh. The study also has found some interventions that may play a critical role in reducing school dropout. Data had been collected from the industrial area of Tongi named Tetul-tola Slum, Kolabagan, Tongi, and secondary data had been collected from published Govt. Research papers. The data demonstrate that not only the economic background, parents unwillingness to education, parents education level, the distance of a school, gender discrimination, low quality of education, security problem of girls in school, teachers’ behavior, even students’ unwillingness to go to school and earning money in early age are the key reasons of children drop out from school. However, girls are more likely to drop school than boys.